A Dissection of Trading Capital: Trade in the Aftermath of the Fall of the Iron Curtain. (29th June 2018) - Beestermöller, Matthias; Rauch, Ferdinand
Abstract : We study trade in Europe after the fall of the Iron Curtain, and show that the countries of the former Austro-Hungarian monarchy trade significantly more with one another after 1989 than predicted by a standard gravity model. Cultural trading capital, established under Habsburg rule and maintained in the period of the Iron Curtain, seems to have survived over four decades of separation and gives an initial boost to trade. This surplus trade disappeared rapidly after 1990 as countries rearranged themselves with the new geopolitical circumstances. We document the rate of decay of these forces.